2017
DOI: 10.1002/2016gl071006
|View full text |Cite
|
Sign up to set email alerts
|

Submesoscale cyclones in the Agulhas current

Abstract: Gliders were deployed for the first time in the Agulhas Current region to investigate processes of interactions between western boundary currents and shelf waters. Continuous observations from the gliders in water depths of 100–1000 m and over a period of 1 month provide the first high‐resolution observations of the Agulhas Current's inshore front. The observations collected in a nonmeandering Agulhas Current show the presence of submesoscale cyclonic eddies, generated at the inshore boundary of the Agulhas Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 30 publications
4
49
0
Order By: Relevance
“…The triggering of the barotropic instability along the Agulhas inshore front is compared between the model and the SAGE data. With the 1‐month long glider dataset, a partial trueHRS term can be computed along a cross‐front section at 25.75° E (Krug et al, ). This partial term accounts for the cross‐front derivative subterms: trueuvytrueutruevvytruev, the overbar denotes a monthly time average, which corresponds to the full SAGE period, and the prime denote fluctuations relative to this time mean.…”
Section: Submesocale Eddies Along the Agulhas Cyclonic Frontmentioning
confidence: 99%
“…The triggering of the barotropic instability along the Agulhas inshore front is compared between the model and the SAGE data. With the 1‐month long glider dataset, a partial trueHRS term can be computed along a cross‐front section at 25.75° E (Krug et al, ). This partial term accounts for the cross‐front derivative subterms: trueuvytrueutruevvytruev, the overbar denotes a monthly time average, which corresponds to the full SAGE period, and the prime denote fluctuations relative to this time mean.…”
Section: Submesocale Eddies Along the Agulhas Cyclonic Frontmentioning
confidence: 99%
“…Using this jet reference frame has shown that three of the five drifters that leaked into the South Atlantic were in the same location relative to the core. These drifters were in a region of high shear that has been linked to the generation of submesoscale cyclones (Krug et al, ). This supports the idea that smaller cyclonic features play a significant role in Agulhas Leakage; this has been shown by Doglioli et al () who found that cyclonic looping trajectories are responsible for 17.4% of Agulhas Leakage.…”
Section: Discussionmentioning
confidence: 99%
“…The region south of 34°S is a key region for the AC system where small‐scale dynamics can have a large impact on the Agulhas leakage and thus on the global ocean. At the northern boundary of the AC, shear‐edge instabilities lead to the formation of meanders, shear‐edge eddies, filaments, plumes, and submesoscale vorticies (Krug et al, ; Lutjeharms et al, ; Lutjeharms, Boebel, et al, ; Lutjeharms, Penven, et al, ). The warm and salty plumes advected from the northern flank of the AC move either onto the Agulhas Bank or drift northwestward into the South Atlantic Ocean as “Agulhas filaments” (Lutjeharms & Cooper, ).…”
Section: Introductionmentioning
confidence: 99%